Effect of Combination Mirror Therapy and Cylindrical Grip on Self-Care of Post-Stroke Ischemic Patients - Bernadetta Germia Aridamayanti; Nursalam Nursalam; Iqlima Dwi Kurnia (Jurnal Ners, 2020)
Introduction: Stroke is the leading cause of disability at a productive age. Hemiparesis upper limb is an example of a disability that is found post-stroke, which limits self-care such as eating, bathing, toileting and dressing. The purpose of this study was to determine the effect of a combination of mirror therapy and cylindrical grip on improving self-care of post-stroke patients.Methods: The design of this study was quasi-experimental (pre-post test with control group design). The population was post-stroke patients who experience upper limb hemiparesis in the Medical Rehabilitation Poly. A sample of 66 respondents (33/33) was chosen using purposive sampling. The independent variable was a combination of mirror therapy and cylindrical grip, and the dependent variable was self-care. Data were collected using a self-care questionnaire with strong validity and reliability. Analysis was undertaken using Kolmogorov Smirnov and Wilcoxon Sign Rank Test. Interventions were given three times a week for a month.Results: In the intervention and control groups there were significant differences between self-care before and after the intervention with a value of 0.000 (p <0.05).Conclusion: The increase in the intervention group can be seen from the sub-variables in self-care toileting, which involves cleaning the genitalia area after defecation/urination. This intervention stimulates the finger sensory and motor nerves so that they can perform self-care to the maximum. A combination of mirror therapy and cylindrical grip has been shown to improve self-care.